(untitled) (Research, Society and Development, 2022)
In 2019, the world became aware of the “severe acute respiratory syndrome coronavirus-2” (SARS-CoV-2). The SARS-CoV-2-associated disease “coronavirus disease 2019” (COVID-19), which has become the biggest current public health problem, was declared a pandemic on March 11, 2020. The consequences of this pandemic were felt in important areas. society, such as education. Therefore, this study aimed to describe the main impacts on the teaching and learning of children and adolescents during the COVID-19 pandemic. A systematic review was carried out on articles published in the journals platform of the Coordination of Improvement of Higher Level - CAPES, in the LitCOVID database of the National Library of Medicine with a search until March 8, 2021, where articles that were selected for evaluation were selected for evaluation. contained the descriptors "schools", "closing, reopening, repercussions, learning losses" and "COVID-19, impacts of the pandemic, Coronavirus, SARS-CoV-2". They highlighted as impacts, the social crisis, the health crisis, ruptures in the educational process, the exclusion of students due to the low power of acquisition of technologies necessary for remote classes, the latent inequality, the damage in obtaining the contents these negatively affect the process of teaching and learning during the pandemic. This process was abruptly interrupted and attempts to continue educational activities were not adequate to provide quality education. The health crisis aggravated the existing social crisis in Brazil, social isolation was definitive. The rupture and vulnerabilities weakened learning, making it difficult to establish knowledge and continue in educational and curricular training.